Interfaces tecnológicos corporales en la práctica artística de María Castellanos - Cueto Puente, Mª de Jesus (2019)
This paper will focus on three projects made by the artist María Castellanos (Gijón, 1985) in collaboration with the mathematician Alberto Valverde. From this artwork, which deals with the figure of the cyborg, we describe the used materials and procedures. From these, they are highlighted digital fabrication tools such as the corporal technological interfaces and the 3D printing